Synthesis and characterization of two novel urethane macromonomers and their methacrylic/urethane graft copolymers - Alshuiref, Abubaker (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Chemistry and Polymer Science))--University of Stellenbosch, 2010.